Corruption and development sustainability: The implications of artificial intelligence as a tool to eliminate corruption in the Era of Society 5.0 in Riau Province - Antony Antony; Jenny Shania (Journal of Law Science, 2024)
This research aims to examine the urgency of the implications of artificial intelligence as a tool to eradicate corruption in the era of society 5.0, especially in Riau Province. This urgency is motivated by the rampant criminal acts of corruption in Riau Province which have resulted in state losses of up to Rp 2.2 trillion. The research method used is normative legal research with literature review. The results of this study show that countering corruption in Riau Province can effectively and efficiently use artificial intelligence technology with new hopes placed on artificial intelligence to become an unbiased anti-corruption agent. The implication of artificial intelligence as a means of combating criminal acts of corruption in Riau Province must be accompanied by adequate preparation.